Politikströmmar och kommunala trafikflöden : en studie av kollektivtrafik i förändring - Rönnbäck, Peder (Luleå tekniska universitet, Samhällsvetenskap, 2006)
During the last few decades sustainable development has become a frequent topic among policy makers. In order to achieve this goal, the local level in the society has been regarded as one of the levels where changes towards a more sustainable development must come about. To this end, the Swedish state has used different instruments of control to influence its municipalities to start these changes. One example is the Local Investment Programme (LIP) which supported many different local investment programmes in Swedish municipalities between 1998-2002. The municipality of Luleå, where changes of the public transportation system were on the political agenda, received in 2000 financial support for a project called Public transportation in change. The aim of the project was to create a more attractive public transportation system, i.e. bus system, in order to get more people to choose the bus for their daily travels. Policy processes are however not always as rational as policy makers might think. Instead, they can sometimes be characterized as an incremental process with sudden changes. In order to conceptualize such processes, especially agenda- setting and decision making, John Kingdon has developed the multiple- streams framework (MS). According to this framework the policy process is separated into three streams; problem, policy and politics. When a window of opportunity opens, a policy entrepreneur with the right skills and institutional position might couple the streams thereby creating a policy change. The aim of this study is to describe and analyze the policy process underpinning the public transportation in Luleå kommun and explain why the process developed the way it did. The purpose is thereby to contribute to the understanding of the problems that are associated with local policy making regarding public transportation and sustainable development. Another aim is to test whether MS is applicable in a local context. The empirical material is made up of documents, interviews with policy makers, material ...